2021
DOI: 10.3389/fnagi.2021.682308
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Mechanisms of Animal-Assisted Intervention in Alzheimer’s Disease: A Hypothetical Review

Abstract: Alzheimer’s disease (AD) is an irreversible neurodegenerative brain disorder with aggregation of amyloid-beta (Aβ) and tau as the pathological hallmarks. AD is the most common form of dementia and is characterized by a progressive decline of cognition. The failure of pharmacological approaches to treat AD has resulted in an increased focus on non-pharmacological interventions that can mitigate cognitive decline and delay disease progression in patients with AD. Animal-assisted intervention (AAI), a non-pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 89 publications
1
3
0
Order By: Relevance
“…One hypothesis relates to the human-animal bond, meaning the relationship between the canine and pediatric participants in AAT, indicating that this bond is a vital part of the therapeutic process and that behaviors would not be modifi ed without the inclusion of canines in participants' plans of care. 21,22 Th is phenomenon is certainly supported in this case study, as the canine was the target of most of Caleb's recorded interactions. Animals may act as a "transitional object" in AAT sessions, allowing children with ASD to practice social skills in a safe environment and then apply learned behavior outside the clinical setting.…”
Section: ■ Conclusionsupporting
confidence: 66%
See 1 more Smart Citation
“…One hypothesis relates to the human-animal bond, meaning the relationship between the canine and pediatric participants in AAT, indicating that this bond is a vital part of the therapeutic process and that behaviors would not be modifi ed without the inclusion of canines in participants' plans of care. 21,22 Th is phenomenon is certainly supported in this case study, as the canine was the target of most of Caleb's recorded interactions. Animals may act as a "transitional object" in AAT sessions, allowing children with ASD to practice social skills in a safe environment and then apply learned behavior outside the clinical setting.…”
Section: ■ Conclusionsupporting
confidence: 66%
“…Moreover, further insight into the mechanism of action by which animal interaction produces therapeutic effects for children with ASD who are participating in AAT sessions is required to create evidence-based intervention programs. One hypothesis relates to the human-animal bond, meaning the relationship between the canine and pediatric participants in AAT, indicating that this bond is a vital part of the therapeutic process and that behaviors would not be modified without the inclusion of canines in participants' plans of care 21,22. This phenomenon is certainly supported in this case study, as the canine was the target of most of Caleb's recorded interactions.…”
Section: Discussionmentioning
confidence: 67%
“…To date, pharmacological treatments for dementia have had limited effectiveness, are expensive, and are often accompanied by side effects (Jessop et al, 2017; Patterson, 2018). Non-pharmacological therapy has emerged as an essential, economical and alternative treatment to reduce BPSD and alleviate cognitive decline (Abraha et al, 2017; Kim et al, 2021; Leng et al, 2020). Studies have found that animal assisted intervention (AAI) is a popular type of non-pharmacological therapy (Leng et al, 2020) and psychosocial intervention (Barrière et al, 2021) which can have positive effects on physical, psychological, and social functioning of people living with dementia (Chang et al, 2021; Forget et al, 2021; Marks & McVilly, 2020; Yakimicki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Such human-animal interaction can stimulate motivation and positive feelings when people living with dementia interact with animals (Hu et al, 2018; Ritchie et al, 2021). Kim et al conducted a neurological perspective analysis to interpret the mechanism of AAI, through sensory interactions with animals to improve emotional and social activities, thereby to counter Aβ deposition, tau hyperphosphorylation and neuroinflammation related to Alzheimer’s disease pathologies (Kim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%